Decision-Making Employee Performance Evaluation at XYZ University Using the Mamdani Fuzzy Logic Method - Irvan Syah Riadi; Fahmi Fauzi; Arsal Adriana Yusuf; Muchtar Ali Setyo Yudono (Universitas Nusa Putra, 2021)
Human resources (HR) of high quality will provide excellent job outcomes. Through the execution of quality and quality education, human quality is developed. As a tool for assessing the quality of education in Indonesia, the evaluation of a lecturer's performance plays a crucial role in education. This research intends to aid in assessing the performance of Lecturers using Fuzzy Logic. Mamdani is the fuzzy logic approach used in this study. The assessment input factors consist of Lecturer Presence in Teaching, Discipline Level, Student Assessment Results, loyalty, and Communication Level or engagement with students to provide two judgments based on a Lecturer's poor and excellent performance. This system may assist and give options for assessing the performance of Lecturers, allowing Lecturers to make optimum adjustments to recruit the most outstanding and competent lecturers. Based on the study findings, it can be inferred that an intelligent system based on fuzzy logic may be utilized to identify Lecturer performance judgments with a 90 percent degree of accuracy